2015
DOI: 10.3906/biy-1411-23
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and assessment of the phytoremediation potential of duckweed for triarylmethane dye degradation with the emphasis on some physiologicalresponses and effect of operational parameters

Abstract: Phytoremediation is a low-cost and effective technology that removes pollutants, such as dye-containing effluents, from the environment through the use of plants. In the present study, the potential of Lemna minor L. for decolorization and degradation of the triarylmethane dye malachite green was investigated. The results revealed that the decolorization ability of the plant species is as high as 88%. The effect of some operational parameters (initial dye concentration, temperature, pH, and amount (weight) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Higher root metal concentrations and lower shoot metal concentrations at higher dose indicate restriction of Cd from the root to aerial parts via xylem sap flow. The present work, as well as Ertekin et al (2015) on Landoltia punctata and Torbati (2015) on Lemna minor, indicated the usefulness of aquatic plants for phytoremediation purposes for various pollutants. Thus, the present study showed that E. crassipes accumulated high amounts of Cd and responded well at physiologically phytotoxic Cd concentrations.…”
Section: Bioconcentration Factor (Bcf) and Translocation Factor (Tf) Of Cadmiumsupporting
confidence: 60%
“…Higher root metal concentrations and lower shoot metal concentrations at higher dose indicate restriction of Cd from the root to aerial parts via xylem sap flow. The present work, as well as Ertekin et al (2015) on Landoltia punctata and Torbati (2015) on Lemna minor, indicated the usefulness of aquatic plants for phytoremediation purposes for various pollutants. Thus, the present study showed that E. crassipes accumulated high amounts of Cd and responded well at physiologically phytotoxic Cd concentrations.…”
Section: Bioconcentration Factor (Bcf) and Translocation Factor (Tf) Of Cadmiumsupporting
confidence: 60%
“…Due to the simple structure and morphology, high growth rate, and small size of Lemna species, these plants have many applications in ecotoxicological studies. Their sensitivity to different classes of pollutants and easy cultivation make them suitable for such investigations (Zezulka et al, 2013;Torbati, 2015). Among many types of NPs, zinc oxide (ZnO) NPs have a wide range of applications, including sunscreens, solar cell coatings, pharmaceutical processes, food additives, and semiconductors (Yoo et al, 2005;Yoon et al, 2014;Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the simple structure and morphology, high growth rate, and small size of Lemna species, these plants have many applications in ecotoxicological studies. Their sensitivity to different classes of pollutants and easy cultivation make them suitable for such investigations (Zezulka et al, 2013;Torbati, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the potential of L. minor for decolorization and degradation of malachite green (a triarylmethane dye) was investigated. The decolorization ability of the plant species was as high as 88%, and eight metabolic intermediate compounds were identified by gas chromatography-mass spectrometry [ 108 ]. Can-Terzi et al (2021) [ 109 ] studied the phytoremediation potential of L. minor using methylene blue and showed that L. minor could effectively remove methylene blue from wastewater with the highest removal efficiency (98%) within 24 h. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) analyses indicated that dye removal was mainly by biosorption.…”
Section: Duckweeds For Remediating Water Contaminated With Organic Co...mentioning
confidence: 99%